Hemşirelerde empatik eğilim ve iş doyumu ilişkisi - Cengiz, Serpil (My University, 2008)
) ÖZET Araştırma, hemşirelerin empatik eğilim ve iş doyumu düzeyleri ile bunların birbirleriyle olan ilişkisini saptamak amacıyla tanımlayıcı ve ilişki arayıcı olarak gerçekleştirildi. Şubat-Nisan 2008 tarihlerinde İstanbul’da bir tıp fakültesi hastanesinin genel cerrahi ve iç hastalıkları anabilim dallarına bağlı servis ve poliklinikler ile yoğun bakımların tümünde çalışan ve araştırmaya katılmaya gönüllü toplam 263 hemşire araştırmanın örneklemini oluşturdu. Veri toplanmasında araştırmacı tarafından hazırlanan bilgi formu, Dökmen tarafından geliştirilen Empatik Eğilim Ölçeği ve Türköz tarafından geliştirilen İş Doyumu Ölçeği kullanıldı. Veri analizinde; t testi, tek yönlü varyans analizi, Tukey-Hsd, pearson korelasyon, nonparametrik spearman korelasyon analiz teknikleri kullanıldı. Sonuçlar ortalama, standart sapma cinsinde sunuldu. Empatik Eğilim Ölçeğinin Güvenirliğinin Cronbach’s Alpha katsayısı 0.73, İş Doyumu Ölçeğinin Güvenirliğinin Cronbach’s Alpha katsayısı 0.94 bulundu. İş doyumuna ait 7 alt ölçeğin puanlarından elde edilen cronbach-alfa güvenilirlik katsayısı 0.81 olarak bulundu. Anlamlılık p<0.05 düzeyinde ele alındı. 263 kişinin çalışma süresi ortalaması 10.88 ± 8.54 yıl, bulunduğu birimde çalışma süresi ortalaması 6.80 ± 6.48 yıl ve genel yaş ortalaması ise 32.02 ± 7.84 olarak bulundu. Kişisel ve mesleki değişkenlerin bazılarının iş doyumunu etkilediği saptandı ancak bu değişkenlerin empatik eğilim düzeyi üzerinde istatistiksel anlamda etkisi saptanmadı. Empatik eğilim toplam puanı ile iş doyumunun diğer alt boyut puanları ve iş doyumu toplam puanı arasında hiçbir anlamlı ilişki bulunmadı (p>0.05). İş doyumu toplam puanı ile iş doyumu ölçeğinin tüm alt boyutları arasında ve alt boyutların birbirleriyle olan ilişkilerinde istatistiksel olarak anlamlı, aynı yönde ve kuvvetli ilişki saptandı (p<0.05). empatik eğilim, hemşire, iş doyumu )

The Relation Between Emphatic Tendency And Job Satisfaction for Nurses The research had been performed about the levels of the relation between emphatic tendency and job satisfaction of nurses and as defining and searching a relation with the aim of setting the relation between them. The nurses, totaly 263, who involved in research voluntarily, and who have been studying at services and polyclinics connected to department branches of general surgery, internal diseases and intensive care unit of a university medical faculty in İstanbul in February-April 2008, had formed the sample of research. The information form prepared by the researcher during collecting data, the scale of emphatic tendency which had reformed by Dökmen and the scale of job satisfaction which had reformed by Türköz were used. In data analysis; t-test, one way variance analysis, Tukey-Hsd, pearson correlation, non-parametric spearman correlation analysis techniques were used. The results were offered in terms of mean, standart deviation. Cronbach’s Alpha coefficient of the confidence of the scale of emphatic tendency is 0.73, cronbach’s alpha coefficient of the confidence of the scale of job satisfaction is 0.94. The coefficient of the confidence of cronbach-alpha that obtained from the points of 7 sub scales belong to job satisfaction was found as 0.81. Significance was treated at the level p<0.05. The mean of working duration of 263 person was found as 10.88 ± 8.54 years, the mean of working duration in her/ his unit was found as 6.80 ± 6.48 years and the mean of general age was found as 32.02 ± 7.84 years. Some of personal and career variables were treated as affected the job satisfaction, but the effect of these variables in statistical meaning on the level of emphatic tendency was not determined. Among total point of emphatic tendency and the other sub-dimension points of job satisfaction and the total point of job satisfactin was not found any significance relation (p>0.05). Between the total points of job satisfaction and all sub dimensions of job satisfaction scale, and in the interrelations of sub dimensions, was determined significant as statistical, in the same direction and strong relation (p<0,05). emphatic tendency, job satisfaction, nurse.
Keywords: Empati_Psikoloji; Hemşirelik_İş Tatmini; Hemşirelik_Psikoloji; İş Tatmini